Study of Utilization of Embedded Metal Nanoparticles in Dielectric Thin Film for Humidity Sensing - Hala J. El-Khozondar; Waleed S. Mohammed (Photonic Sensors, 2019)
Abstract This paper presents a theoretical study of the utilization of the shift in the reflection peak of the thin dielectric film with embedded metal nanoparticles (NPs) towards humidity and vapor applications. The presence of the NPs in the film results in a complex effective index. Hence, the reflected light at the superstrate-film interface causes a phase shift when the index of the surrounding is changed. This alters the reflected spectrum of the formed Fabry-Perot, for both the reflection peak wavelength and intensity. Here, the dynamic range of the proposed sensor is optimized through the variation of the film thickness and nanoparticle metal type, as well as the volume fraction.